An anti-humanist acquittal: 'Résistantialisme' and the lettrist defense of Louis-Ferdinand Céline. Issue 9 (1st September 2020) - Hussey, Andrew
ABSTRACT: In 1949 the novelist Louis-Ferdinand Céline was languishing in exile in Denmark, having fled a warrant that had been issued for his arrest on charges of collaboration during the Occupation. Having been one of the most successful writers of the 1930s, Céline was now one of the most hated men in France; a notorious anti-semite. During this period the lettristes Maurice Lemaître and Isidore Isou, both Jews, decided launch a campaign to defend Céline. This was meantas a severe provocation to the right-thinking intelligentsia on the Left Bank who were so hypocritical and so quick to condemn Céline, whilst many of their crimes went unpunished. But what really brought Céline and the young Jews together was that they both shared a special contempt for Jean-Paul Sartre. More precisely all three of them them had been particularly incensed for parallel reasons, by an article Sartre had published in 1945 in the journal Les Temps Modernes called 'Portrait of an anti-Semite'. This article will explore why this piece had so incensed the three men, and what their contribution was to the politics of post-war Paris. More to the point the polemic against Sartre marks a shift from Humanism in French politics.